Analisis Peramalan Permintaan Dalam Menentukan Perencanaan Pengadaan Barang Dengan Penerapan Metode Exponential Smoothing Pada Usaha Dagang Serbi.smr di Kota Samarinda (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Forecasting analysis using the Exponential Smoothing method is a tool in carrying out forecasting calculations for the procurement of goods in the future. The Exponential Smoothing method perfoms smoothing on the periodic data series that will be tested. Exponential Smoothing carries out data test using historical data for a predetermined period and calculating the constant weight value which has the lowest erorr value. The results of the research explain that this method is used a measuring tool determine the procurement of goods in the required quantity so that in the future business actors can continue to run their business in a structures, planned, optimal manner and in its development business actors can make in-depth and subjective business decisions. Keywords: Exponential Smoothing, Forecasting, Historical Data
Keywords: Exponential Smoothing, Peramalan, Data Historis